ANALISIS LAPORAN KEUANGAN PT.BPR JATIM UNTUK MENGETAHUI KINERJA DAN KESEHATAN BANK PERIODE (2013-2015) - Fakhrudin, Fakhrudin; Hidayat, M. Taufiq (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTResearch aims to acknowledge financial performance of property company listing in the BEI during period 2011-2014 if it is analyzed using financial ratio analysis with Du Pont System Analysis approach Cross Sectional. Financial ratio analysis with Du Pont System Analysis approach is an analysis to show the relationship between NPM, asset circulation, debt and ROI to determine company ROE. Type of research is kuantitatif descriptive. Data source includes primary and secondary data. Data collection technique is documentation. Based on the result of research, financial performance PT. Lippo Cikarang Tbk is quite good progress barn has show the metode of Time Series Analysis that ROI over four years in a stable condition that equel to 12,56%, 14,46%, 15,10%, 19,78% and averange ROI 2011-2014 is equel to 15,48%. And ROE 31,28%, 33,41%, 32,00%, 31,85% dan averange ROE 2011-2014 is equel to 32,14%. Thought the Cross Sectional method, the company is located above on top the average standart property company.Financial performance PT. Megapolitan Development, Tbk with ROI equel to 0,22%, 0,46%, 3,62%, 3,76% and averange ROI 2,02%. And ROE 0,38%, 0,78%, 6,09%, 7,37% dan averange ROE 2011-2014 is equel to 3,66%. Thought the the Cross Sectional, the company is located below the property industry everange. Keyword: Du Pont System, Financial Ratio, Financial performance